Rate of force development, muscle architecture, and performance in elite weightlifters - Zaras, N.; Stasinaki, A.-N.; Spiliopoulou, P.; Arnaoutis, G.; Hadjicharalambous, M.; Terzis, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The purpose of the present study was to investigate the relationship between weightlifting performance and the rate of force development (RFD), muscle architecture, and body composition in elite Olympic weightlifters. Methods: Six male Olympic weightlifters (age 23.3 [3.4] y, body mass 88.7 [10.2] kg, body height 1.76 [0.07] m, snatch 146.7 [15.4] kg, clean and jerk 179.4 [22.1] kg), all members of the national team, participated in the study. Athletes completed a 16-week periodized training program aiming to maximize their performance at the national competition event. Measurements, including maximal strength (1-repetition maximum) in snatch, clean and jerk, back and front squat, isometric leg press RFD and peak force, countermovement jump, vastus lateralis muscle architecture, and body composition, were performed before and after the training period. Results: Weightlifting performance increased significantly after training (P < .05). Leg press RFD increased only in time windows of 0 to 200 and 0 to 250 milliseconds after training (8.9% [8.5%] and 9.4% [7.7%], respectively, P < .05) while peak force remained unaltered (P < .05). Front squat strength increased significantly (P < .05), while countermovement jump power increased 2.3% (2.1%) (P < .05). No changes were observed for muscle architecture and lean body mass (P > .05). Significant correlations were observed between performance in snatch and clean and jerk with isometric leg press RFD, at all time windows, as well as with lean body mass and squat 1-repetition maximum. Conclusions: These results suggest that regular examination of RFD, lean body mass, and lower extremities` 1-repetition maximum may be useful performance predictors in elite Olympic weightlifters.